EMPLOYING SEMANTIC WEB TECHNOLOGIES TO PROVIDE DYNAMIC CONTENT FOR ELECTRONIC MUSEUM GUIDES - Kuper, Heinz-Günter (International Journal of Computing, 2010)
Tim Berners-Lee’s vision of the Semantic Web promises to make the targeted retrieval of online information far more accurate. As Semantic Web technologies mature, software systems will be able to deliver detailed information regarding particular artefacts on the fly in a museum environment, thus answering visitor queries that were not anticipated by the content creators. This paper explores some of the issues associated with providing such a solution.